PERTUMBUHAN KELAPA SAWIT DENGAN PEMBERIAN PUPUK ORGANIK ASAL PELEPAH KELAPA SAWIT DENGAN ASAM HUMAT - Mira Ariyanti; Yudithia Maxiselly; Santi Rosniawaty; Rachman Achmad Indrawan (Jurnal Penelitian Kelapa Sawit, 2019)
Increased productivity of oil palm is a major challenge in Indonesia's oil palm plantations. The application of inorganic fertilizers is still ongoing and requires consideration to reduce its use, given the excessive application can reduce the physical and chemical conditions of the soil. The action that can be done is by utilizing palm oil stem waste and humic acid. This research aims to observe the influence of oil palm midrib organic fertilizer and humic acid with various compositions to the young oil palm. The experiment was conducted from December 2017 to March 2018 in Experimental Station of Ciparanje, Faculty of Agriculture, Universitas Padjadjaran, Sumedang. Experiment used a randomized block design with 9 treatments and 3 replications. The treatments consisted of inorganic fertilizer NPKMg 500 gram/plant, 1600 gram/plant of oil palm midrib compost, 3200 gram/plant of oil palm midrib compost, combination of 1600 gram/plant of oil palm midrib compost and humic acid 15 ml/plant, 20 ml/plant and 45 ml/plant, and the combination of 3200 gram/plant of oil palm midrib compost and humic acid 15 ml/plant, 30 ml/plant and 45 ml/plant. The results of this experiment showed that 3200 gram of oil palm midrib compost and 30 ml of humic acid gave the best influence towards the height plant and chlorophyll content in 4 months after treatment.